CMOS stimulating chips capable of wirelessly driving 473 electrodes for a cortical vision prosthesis. (19th February 2019) - Wong, Yan T; Feleppa, Timothy; Mohan, Anand; Browne, Damien; Szlawski, Julian; Rosenfeld, Jeffrey V; Lowery, Arthur
Abstract: Objective . Implantable neural stimulating and recording devices have the potential to restore capabilities such as vision or motor control to disabled patients, improving quality of life. Implants with a large number of stimulating electrodes typically utilize implanted batteries and/or subcutaneous wiring to deal with their high-power consumption and high data throughput needed to address all electrodes with low latency. The use of batteries places severe limitations on the implant's size, usable duty cycle, device longevity while subcutaneous wiring increases the risk of infection and mechanical damage due to device movement. Approach . To overcome these limitations, we have designed and implemented a system that supports up to 473 implanted stimulating microelectrodes, all wirelessly powered and individually controlled by micropower application specific integrated circuits (ASICs). Main results . Each ASIC controls 43 electrodes and draws 3.18 mW of power when stimulating through 24 channels. We measured the linearity of the digital-to-analog convertors (DACs) to be 0.21 LSB (integrated non-linearity) and the variability in timing of stimulation pulses across ASICs to be 172 ns. Significance . This work demonstrates the feasibility of a new low power ASIC designed to be implanted in the visual cortex of humans. The fully implantable device will greatly reduce the risks of infection and damage due to mechanical issues.